Evaluation of inter-observer variability according to RECIST 1.1 and its influence on response classification in CT measurement of liver metastases. Issue 95 (October 2017) - Bellomi, Massimo; De Piano, Francesca; Ancona, Eleonora; Lodigiani, Alessandra Ferla; Curigliano, Giuseppe; Raimondi, Sara; Preda, Lorenzo
Highlights: RECIST measurements are reproducible on a large and heterogeneous population of Radiologists. Older and more experienced Radiologists performed better in measuring hepatic lesions. The evaluation of response rate on CT are considered pivotal in the response to anticancer chemotherapy. A second opinion or a central revision by skilled Radiologists is mandatory to assess response in clinical trials. Abstract: Objective: The aim of this study is the evaluation of inter-observer variability in the measurement of liver metastases according to RECIST and its influence on response classification. Patients and methods: A total of 100 radiologists measured liver target lesions, on pre- and post-chemotherapy CT scans of three patients. Each observer filled out a questionnaire about his personal and work features. The evaluations of a well experienced radiologist, considered as "the gold standard", were compared to those taken by the observers. The percentage of the observers in agreement with the reviewer, in terms of the response category and in terms of inter-observer variability, was calculated for each patient. Results: The percentage of the inter-observer agreement was elevated. Most of the observers in agreement with the reviewer were senior radiologists, while those who disagreed were junior radiologist, but this result did not reach a statistical significance. More than 30% of observers disagreed with the reviewer at least in one of the three cases. Conclusions: RECIST measurements are reproducible on a large and heterogeneous population of radiologists. Age and expertise of the radiologist remain the most critical factors: this suggests a revision by well-experienced radiologists in clinical trials.